2021
DOI: 10.1016/j.psj.2021.101192
|View full text |Cite
|
Sign up to set email alerts
|

Research Note: Intestinal morphology and gene expression changes in broilers supplemented with lysolecithin

Abstract: Lysolecithin is used as a feed additive to aid fat digestion and absorption in broiler chickens. Previous research has shown that dietary fat source influences how broilers respond to lysolecithin supplementation. Therefore, the objective of this study was to investigate the effect of lysolecithin on a diet formulated with soybean oil on jejunum morphology and expression of selected genes in broiler chickens. Male Cobb 500 chickens were fed a Control diet or the Control diet supplemented with lysolecithin ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The morphological improvements could result from the synergistic effects of emulsifier interactions with the other feed ingredients as opposed to the influence of the emulsifier in isolation [27]. However, variations could also exist with no significant effects of emulsifiers on gut morphology being previously reported [28].…”
Section: A C C E P T E Dmentioning
confidence: 98%
“…The morphological improvements could result from the synergistic effects of emulsifier interactions with the other feed ingredients as opposed to the influence of the emulsifier in isolation [27]. However, variations could also exist with no significant effects of emulsifiers on gut morphology being previously reported [28].…”
Section: A C C E P T E Dmentioning
confidence: 98%
“…Furthermore, Cloft et al (2021) reported that the addition of lysolecithin led to the upregulation of carbonic anhydrase VII and interleukin 8‐like 2, which have been also associated with better gut health (see Table 3). However, variations could also exist with no significant effects of emulsifiers on gut morphology being previously reported (Tenório et al, 2022; Wickramasuriya, Cho, et al, 2020).…”
Section: Application Of Exogenous Emulsifiersmentioning
confidence: 99%